Identifikasi Risiko Ergonomi pada Pekerja Tenun di Kecamatan Dawan Kabupaten Klungkung - Putu Santi Pridayanti; Ni Wayan Rusni; Putu Nia Calista Santoso (Aesculapius Medical Journal, 2023)
Weaving is a job that requires high accuracy. Weaving workers work on problems such as sitting posture, repetitive worker movements, and non-ergonomic tool designs, which often cause fatigue and musculoskeletal disorders (MSDs). This study aimed to look at the risk description of work attitudes, workload, fatigue and MSDs complaints on weaving workers in Dawan District, Klungkung Regency. The subjects in this study were weaving workers in Dawan District, Klungkung Regency. This research was conducted using a descriptive observational study with a cross sectional study design. The research was conducted in June – August 2022 using purposive sampling technique and obtained 40 respondents of weaving workers in Dawan District, Klungkung Regency. Data were obtained through interviews, filling out questionnaires, and direct measurements. The data was analyzed using SPSS Type 26 with univariate analysis. The final results showed 57.5% of moderate risk work attitudes, 62.5% of light physical workloads, 52.5% of very high mental workloads, 50% had a moderate level of fatigue and 45% had a low level of MSDs. Ergonomics work attitude plays an important role in the condition and health of weaving workers. Therefore, it is necessary to evaluate the design of the work environment to minimize the occurrence of work fatigue and MSDs complaints.